A dimensão dialógica do literário na obra de António Lobo Antunes - Lázaro, Débora (2020)
Novel and poetry are literary fields which have always provided fertile dialogues with psychology’s clinical dimension. By extension, the creative gesture, in its attitude of creation, contributes to think of the human being as a builder of himself in relation to the other. This thesis has as foundation the poetic prose of the writer António Lobo Antunes in his inaugural trilogy: Memória de Elefante, Os Cus de Judas e Conhecimento do Inferno. By having a deep look, in an essayistic and dialogical way, the creative act through the themes of conflict, strangeness, dialogue and memory, through interchanges with other artistic (music, cinema and visual arts), essayistic and philosophical areas